PENGARUH TERAPI KOMBINASI RELAKSASI TERHADAP TINGKAT KECEMASAN PASIEN HEMODIALISA - Rama Ariwijaya (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
Hemodialysis is the process of removing metabolic waste from other toxic substances through a semipermeablemembrane as a separator between blood and dialysate fluid which is deliberately made in a dializer. Management ofhemodialysis, can cause pain in the fistula puncture area, it can cause anxiety in patients. Furthermore, the length ofthe hemodialysis process, the threat of death, changes in self-concept, dependence on others, difficulties inmaintaining work, financially, changing roles and changing social interactions can also be a cause of the emergenceof psychological effects namely anxiety in hemodialysis patients. This study aims to determine the effect ofrelaxation combination therapy on the anxiety level of hemodialysis patients. This research is a quantitative quasiexperimental study using a pretest-posttest control group design. This research was conducted at Palembang PusriHospital on 40 patients based on purposive sampling technique. The results showed there was a significant influencebetween anxiety levels on the administration of relaxation combination therapy interventions by showing that theanxiety level of the intervention group was dominated by mild anxiety at posttest, and in the control groupdominated by moderate anxiety at posttest. Data analysis using the mann-whitney test showed that there weresignificant differences between the anxiety levels of hemodialysis patients before and after relaxation combinationtherapy with p value = 0.013. This study proves that combined relaxation therapy has a significant effect in reducinganxiety levels in patients with CKD undergoing hemodialysis and can be used as nursing interventions.